Diffusion and precipitation phenomena across layer interfaces in a roll bonding composite of Al(Si) and Al(Cu) - Quadir, Md Zakaria; Lau, K.; Afrin, N.; Ferry, M. (VSP BV, BRILL ACADEMIC PUBLISHERS, 2015)
Layered composite structures can be generated in metallic sheets by roll bonding of dissimilar metals/alloys. In this investigation, heat treatable (Al(Cu)) and non-heat treatable (Al(Si)) aluminium alloys are roll bonded in sheet form. Large hardness differences between layers poses significant bonding challenges in the form of multiple necking within the hard Al(Cu) layers. For successful processing, it is vital to choose the candidate materials in a state of marginal hardness differences during rolling, but being capable of altering properties through subsequent heat treatments. Atomic diffusion takes place during heat treatment of the composite sheet and results in gradual hardness variation across sheet thickness. The Al(Cu) layers contribute to strength, whereas the Al(Si) layers provide protection from corrosion/wear-related degradation in the newly developed hybrid sheet. The overall mechanical properties of the heat-treated composite fall between the base alloys. The bonding interfaces are noted as the potential spots for initiating failure.